2017
DOI: 10.1101/221572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the effects of variation in viremia on mosquito susceptibility, infectiousness, andR0of Zika inAedes aegypti

Abstract: Zika virus (ZIKV) is an arbovirus primarily transmitted by Aedes mosquitoes. Like most viral infections, ZIKV viremia varies over several orders of magnitude, with unknown consequences for transmission. To determine the effect of viral concentration on ZIKV transmission risk, we exposed field-derived Ae. aegypti mosquitoes to four doses (10 3 , 10 4 , 10 5 , 10 6 PFU/mL) representative of potential variation in the field. We demonstrate that increasing ZIKV dose in the blood-meal significantly increases the pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…During this process, mosquitoes often experience minimal physiological and fitness costs associated with arbovirus replication (Moreno-Garcia et al, 2014;Shaw et al, 2018), highlighting how mosquito vectors are tolerant to arbovirus infection (Lambrechts and Saleh, 2019). Although some work has reported different degrees of fitness costs to mosquitoes during arbovirus infection (Lambrechts and Scott, 2009;Grubaugh et al, 2017;Petersen et al, 2018;, virus proliferation is frequently non-pathogenic and the observed harm is host and pathogen strain-specific (Martin et al, 2010;Reiskind et al, 2010;Tesla et al, 2018;Sirisena et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During this process, mosquitoes often experience minimal physiological and fitness costs associated with arbovirus replication (Moreno-Garcia et al, 2014;Shaw et al, 2018), highlighting how mosquito vectors are tolerant to arbovirus infection (Lambrechts and Saleh, 2019). Although some work has reported different degrees of fitness costs to mosquitoes during arbovirus infection (Lambrechts and Scott, 2009;Grubaugh et al, 2017;Petersen et al, 2018;, virus proliferation is frequently non-pathogenic and the observed harm is host and pathogen strain-specific (Martin et al, 2010;Reiskind et al, 2010;Tesla et al, 2018;Sirisena et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Across all mosquito-virus pairs and all experiments, conditional on exposure, 72% of mosquitoes became infected, 56% of mosquitoes disseminated virus, and 38% transmitted, implying that on average 72% of mosquitoes became infected, 77% of infected mosquitoes developed a disseminated infection, and 68% of mosquitoes with a disseminated infection went on to transmit. Although this method provides only a coarse measure of barrier importance relative to using single studies measuring infection, dissemination, and transmission for each vector – virus pair [41], these results indicate that no single barrier stands out as the sole restriction to transmission ability, suggesting that all three are important.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, ZIKV has been previously shown to disseminate to the heads of Ae . aegypti at a higher rate in a dose-dependent manner [ 29 ]. Likewise, virus detection via amplification in Vero cells allows the conclusion that Starve mosquitoes released higher quantities of ZIKV along with saliva than Control females, although we cannot rule out that the barriers formed by the salivary glands were impaired in Starve mosquitoes.…”
Section: Discussionmentioning
confidence: 99%